Microstructures and wear-resistance of WC-reinforced high entropy alloy composite coatings by plasma cladding: effect of WC morphology - Peng, Yingbo; Zhang, Wei; Li, Tianchen; Zhang, Mingyang; Wang, Li; Hu, Songhao (Surface engineering, 2021)
WC-reinforced FeCoCrNi high entropy alloy (HEA) composite coatings with different WC morphology of spherical and irregular shape, were prepared by plasma cladding. The effects of WC morphology on carbide evolution, WC dissolution, and the wear resistance of the coatings were investigated. The results indicated that the evolution of the massive and fish-bone M 6 C carbides were significantly influenced by the WC morphology, due to the different curvature radius of WC particles. The dissolution mechanism of spherical WC was diffusion, which of irregular WC was decarburization and oxidation. Although irregular WC particles were broken due to the WC→W 2 C transformation, the wear resistance of the coating with irregular WC was relatively stable, only slightly lower than that of spherical WC, because the developed fish-bone carbide in HEA matrix resisted the three-body abrasive wear of broken WC and W 2 C fragments.